Empowering ICT Potentials in English Language Teaching - Dinda Mei Ayu Utami; Prihantoro Prihantoro; Eka Apriani; Jumatul Hidayah; Ciptro Handrianto (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2021)
In the field of English teaching and learning, the Covid-19 outbreak brings a challenge to English lecturers in order to be able to maintain the continuity of English teaching and learning online by using ICT tools effectively. Thus, this study sought to investigate the uses of ICT tools and the barriers related to the uses of ICT tools in teaching English. Drawing upon a qualitative method, 12 English lecturers at IAIN Curup were purposively selected to be the subjects of this study. Interviews and open-ended questionnaire were deployed to garner the data from the subjects, and the data were triangulated and analyzed using an interactive model of analysis. The findings revealed that the English lecturers used various ICT tools in different ways and purposes. However, some barriers led them to some difficulties of using ICT tools. The barriers were such as: not all ICT media that had been prepared either by the institution or personally could be applied properly; difficulty in playing the roles of lecturers, as were usually done without the highly technical ICT media; the difference in expectations between lecturers and students related to the ICT media used; difficulty in building an interactive atmosphere when using ICT media; and difficulty in providing effective learning responses when using ICT media.